KEEFEKTIFAN MEDIA MINIATUR RUMAH PADA PEMBELAJARAN NUMBER HEADS TOGETHER TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA DI KELAS V SD - Tria Alfi Soraya; Joko Siswanto; Veryliana Purnamasari (Universitas Negeri Medan, 2018)
Abstract: The Effectiveness Of Home Miniature Media On The Learning Number Head Together Against Student Learning Outcomes On Learning Mathematics In Class V Primary School. The purpose of this research isto know about the effectiviness house miniature media in learningof number heads togetherfor the student result in learning of mathematics in fifth class of elementary school. This kind ofresearch is quantitative research in form of Quasi Ekperimental Design with Nonequivalent Control Group Design. Research poulation is all of the students in SD Negeri 2 Ngadimulyo Temanggung in academic year 2017/2018. The result of research isto show the improvement. The result from this research is to show that the data of study result in mathematics learning to get the mean of pre-test in control class is 61,3 and experimental class is get 60,65. The study result of pre-test in experimental class gets the mean is 80,5 and then the experimental class gets the mean is 91,3, and base on the t-test result with dk=38 and standard significant is 5% to know t-test is more than t-table (3,95807 > 2,02439), so Ho is rejected. The conclusion is miniature house media in learning of number heads together is effective on result study of the student in mathematics learning. Keywords : Learning of Number Heads Together, Miniature House Media, Study Result Abstrak: Keefektifan Media Miniatur Rumah Pada Pembelajaran Number Heads Together Terhadap Hasil Belajar Siswa Pada Pembelajaran Matematika Di Kelas V SD. Penelitian ini bertujuan untuk mengetahui keefektifan media miniatur rumah pada pembelajaran number heads together terhadap hasil belajar siswa pada pembelajaran matematika di kelas V SD. Jenis penelitian ini adalah penelitian kuantitatif dalam bentuk Quasi Ekperimental Design dengan desain Nonequivalent Control Group Design. Populasi penelitian adalah seluruh siswa SD Negeri 2 Ngadimulyo Temanggung tahun pelajaran 2017/2018. Hasil penelitian menunjukkan peningkatan. Hasil dari penelitian ini menunjukkan bahwa data hasil belajar mata pelajaran matematika mendapatkan skor rata-rata pre-test kelas kontrol 61,3 sedangkan kelas eksperimen mendapatkan rata-rata 60,65. Hasil belajar post-test kelas eksperimen mendapatkan skor rata-rata 80,5 sedangkan kelas eksperimen mendapatkan rata-rata 91,3, serta berdasarkan hasil uji t dengan dk=38 dan taraf signifikan 5% diketahui thitung lebih besar dari ttabel (3,95807 > 2,02439) maka Ho ditolak. Kesimpulannya bahwa media miniatur rumah pada pembelajaran number heads together efektif terhadap hasil belajar siswa pada mata pembelajaran matematika. Kata Kunci : Pembelajaran Number Heads Together, Media Miniatur Rumah, Hasil Belajar